ANALYSIS OF MILK GOAT QUALITY IN THE ETAWA CROSSBREED GOAT FARMING GROUP IN SAMIGALUH DISTRICT, KULON PROGO YOGYAKARTA - Nur Ika Prihanani; Tri Atmojo; Fathur Haryadi; Naela Wanda Dalimunthe; Tifa Restyka Maulina; Vira Kartika Dewi; Maria Intan Ayu Laraswati (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
The increase in demand for milk has not been matched by the level of milk production. One effort to increase the amount of milk production is by increasing the number of milk-producing livestoc. Peranakan Etawa (PE) goat is a superior type of goat that has the potential to be kept as dairy goats and beef goats. This study aims to determine the quality of PE goat milk in the Kulon Progo area, Yogyakarta. Sampling was carried out in the Samigaluh District, Kulon Progo Regency, Yogyakarta. Goat milk samples were taken from 10 farmers in the amount of 13 milk samples from 13 PE goats. Milk quality testing includes acid degree, fat content, and Total Plate Count (TPC) tests. The test results found that the average acid degree was 6.88 °SH, fat content was 5.6%, and the TPC value was less than 5.6x104 CFU/ml. The quality of goat milk based on acid degree, fat content, and TPC tests is known to be appropriate and suitable for consumption according to SNI 3141.1:2011 and Thai Agricultural Standard (TAS) Number 6006-2008. Farmers are required to pay attention to aspects of livestock maintenance management, including feed management, cage sanitation, and milking processes.